Limitational Factors and the Elasticity of Substitution - Kaldor, Nicholas (Review of Economic Studies, 1937)
Journal Article Limitational Factors and the Elasticity of Substitution Get access Nicholas Kaldor Nicholas Kaldor London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 4, Issue 2, February 1937, Pages 162–165, https://doi.org/10.2307/2967613 Published: 01 February 1937